Sham-Controlled Study of Optokinetic Stimuli as Treatment for Mal de Debarquement Syndrome - Mucci, Viviana; Perkisas, Tyché; Jillings, Steven Douglas; Van Rompaey, Vincent; Van Ombergen, Angelique; Fransen, Erik; Vereeck, Luc; Wuyts, Floris L.; Van de Heyning, Paul H.; Browne, Cherylea J. (Frontiers in Neurology, 2018)
Introduction: Mal de Debarquement Syndrome (MdDS) is a condition characterised by a perception of self-motion in the absence of a stimulus, with two onset types: Motion-Triggered and Spontaneous. Currently, the pathophysiology is unknown and consequently, the therapeutic options are limited. One proposed treatment protocol, developed by Dai and colleagues is based on optokinetic stimulation, which aims to re-adapt the vestibular ocular reflex. This study aimed to reproduce the treatment protocol developed by Dai and colleagues and to assess if a placebo effect is present in the treatment protocol and lastly, aimed to further investigate the treatment on MdDS patient outcomes. Method: Twenty-five MdDS patients (13 Motion-Triggered and 12 Spontaneous) were exposed to five consecutive days of optokinetic treatment (consisting of exposure to optokinetic stimuli with head movements). Eleven of these twenty-five patients were also exposed to two days of a sham treatment prior to the OKN treatment. Posturography measurements and reported symptoms (e.g. using the visual analogue scale (VAS)) of patients were assessed throughout the treatment. Posturography data of the patients was compared with the data of twenty healthy controls. Results: No placebo effect was recorded with any changes in postural data and VAS scale. After the optokinetic treatment, a significant improvement in postural control was observed in 48% of patients, of whom 70% were of the Motion-Triggered subtype (p-values: Area under the Curve - Anterior Posterior <0.001; Area under the Curve – Medio Lateral p <0.001, Confidence Ellipse Area (CEA) <0.001, Velocity <0.001). Conclusion: The protocol was effective in approximately half of the MdDS patients that took part in the study, with no placebo effect recorded. The Motion-Triggered group responded better to treatment than the Spontaneous group. In addition to this, this study indicates that the greatest postural changes occur within the first three days of treatment, suggesting that a shorter protocol is possible. Overall, these findings support what was previously observed in Dai’s studies, that optokinetic stimulation can reduce and ease self-motion perception in those with MdDS. Thus, validating the reproducibility of this protocol, suggesting that a consistent and uncomplicated implementation across treatment centres is possible.